The effect of ammonium sulfate on the growth rate, pigment levels and carrageenan properties of two varieties of kappaphycus alvarezii (Rhodophyta). - Gonzalez, Maria Kristina Senon
Two varieties of Kappaphycus alvarezii (var. Tambalang and var. Bayot) were evaluated for growth rate, carrageenan properties, pigment levels and proximate analysis of nitrogen. Ammonium sulfate of three different concentrations were used as fertilizer (0.025, 0.50 and 1.0 mM). Seaweeds without fertilizer served as the control. Water parameters such as pH, salinity, temperature, and N-P levels in seawater were also observed. A culture of 8 weeks was observed. Results obtained showed that variety 1 gave the highest growth rate when treated with only 0.5 mM while variety 2 obtained its peak growth rate with a treatment of 1.0 mM of ammonium sulfate. Both varieties reached their maximum growth rate at the 8th week of culture. Pigment levels showed decreasing levels at the end of the culture period. Variety 1 gave lower carrageenan yields () but lower and better gelling and melting temperatures, lower values for sulfate content), the highest viscosity at 237.5 cps, lowest crude fiber value of 5.68 ( and a high ash content () of 25.61. Variety 2 gave highest levels of carrageenan yields () at 81+2.07 and highest gel strength at 3.80.0+6.03.